2018
DOI: 10.1016/j.jacc.2018.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of GATA3-Positive Macrophages Improves Cardiac Function Following Myocardial Infarction or Pressure Overload Hypertrophy

Abstract: We demonstrated that the presence of GATA3-positive macrophages adversely affects remodeling of the myocardium in response to ischemia or pressure overload, whereas the absence of these macrophages led to a significant improvement in cardiac function. Targeting of signaling pathways that lead to the expression of GATA3 in macrophages may have favorable cardiac outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 72 publications
1
49
0
Order By: Relevance
“…Effect of M2 macrophages on HSV-1 infection M2 polarization of macrophages in the HSV-1 ocular infection, we used myeloid-specific GATA3-defieicnt mice (designated as M2 -/mice hereafter) [29]. We have previously reported that the cardiac function is significantly improved in M2 -/mice compared with the WT in response to ischemic injury [29].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of M2 macrophages on HSV-1 infection M2 polarization of macrophages in the HSV-1 ocular infection, we used myeloid-specific GATA3-defieicnt mice (designated as M2 -/mice hereafter) [29]. We have previously reported that the cardiac function is significantly improved in M2 -/mice compared with the WT in response to ischemic injury [29].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Effect of M2 macrophages on HSV-1 infection M2 polarization of macrophages in the HSV-1 ocular infection, we used myeloid-specific GATA3-defieicnt mice (designated as M2 -/mice hereafter) [29]. We have previously reported that the cardiac function is significantly improved in M2 -/mice compared with the WT in response to ischemic injury [29]. We have shown that this improvement was associated with the presence of large number of pro-inflammatory Ly6C hi monocytes/macrophages and few Ly6C lo reparative macrophages in the infracted myocardium of M2 -/mice compared with the WT mice.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…In study of Pors et al, GATA3 showed obvious role in identifying mesonephric and mesonephric-like carcinomas of the gynecologic tract [40]. However, Yang et al indicated that deficiency of GATA3-positive macrophages improves cardiac function in the patients with myocardial infarction or pressure overload hypertrophy [41]. Since the function of GATA3 and its relationship with miR-374b was vague, it deserved to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes usually originate from myeloid progenitors in the bone marrow. In mice, monocytes are classified into two subsets, the classical Ly-6C high CCR2 high CX3CR1 low and nonclassical Ly-6C low CCR2 low CX3CR1 high subtypes, based on Ly-6C expression levels; the former subtype migrates to the infarcted areas and serves as the main contributor to inflammation, while the latter always persists in the circulation and is responsible for maladaptive remodeling 63 - 65 .…”
Section: Immune Cellsmentioning
confidence: 99%